Intelligence: theories and applications - Holm-Hadulla, Rainer M.; Funke, Joachim; Wink, Michael (Springer International Publishing, 2022)
Chapter 1. The Evolution of Intelligence: A Multi- and Interdisciplinary Review of Concepts and Practical Applications -- Section 1: Biological basics -- Chapter 2. On the neurobiology of intelligence -- Chapter 3. The intelligent play with chances and selection -- Chapter 4. Intelligence in the animal kingdom -- Chapter 5. Intelligence: Evolutionary Biological Foundations and Perspectives -- Chapter 6. When intelligence is impaired -- Section 2: Psychology of Intelligence -- Chapter 7. Intelligence: The psychological view -- Chapter 8. Interpersonal intelligence -- Chapter 9. Development of intelligence in the context of digital media use -- Chapter 10. Metacognitive myopia - obstacle to intelligent behavior and failure of evolution? -- Section 3: Mathematical and Artificial Intelligence -- Chapter 11. Intelligent algorithms and equations? - An approach to the intelligence of mathematical concepts -- Chapter 12. Artificial intelligence and algorithms - true progress or just digital alchemy? -- Chapter 13. Statistics and intelligence - a chequered relationship -- Section 4: Artificial and Human Intelligence -- Chapter 14. Human and artificial intelligence - a critical comparison -- Chapter 15. Emotional robotics - curse or blessing in psychiatric care? -- Chapter 16. Human and artificial intelligence in medicine -- Section 5: Economic Intelligence -- Chapter 17. The idustrialisation -- Chapter 18. Intelligent strategies: Correct recognition and good choices in a complex world -- Section 6: Cultural intelligence -- Chapter 19. Intelligence and literary fiction: How novels can improve our (understanding of) intelligence -- Section 7: Political Intelligence and Wisdom -- Chapter 20. Meta-Intelligence: Understanding, Control, and Coordination of Higher Cognitive Processes -- Chapter 21. Intelligentia Dei - Artificial Intelligence, Human Reason and Divine Wisdom -- Chapter 22. Political intelligence? A practical view between politics and science -- Chapter 23. Political intelligence and wisdom.